Letter to the Editor: Rejoinder - HASAN, Zubair (Turkish Economic Review, 2018)
Turkish Economic Review Volume 5, June 2018 issue 2, contains a letter to the editor from Steve H. Hanke professor at John Hopkins University “on Turkey’s Precarious Economic Situation”, which is imposed on the country by the hegemonic approach of US to international relations with developing economies like Turkey using the trade weapon as President Erdogan puts it. The letter of Hanke carries arrogance, lacks urbanity, and contains much economic nonsense, to put it mildly. Surprisingly, the narration soon assumes a question-answer format as if it were an interview! Let me tear across his main points.